Collaborative product development: a literature overview - Büyüközkan, Gülçin; Arsenyan, Jbid (Production planning & control, 2012)
While recent literature underlines the importance of collaborations in product development, and many studies analyse its applications, this subject is constantly developing and has the potential to expand into new dimensions. Collaborative product development (CPD) has emerged as a new way of business, increasing efficiency and effectiveness in product development. Although joint ventures and strategic alliances may be considered as a relatively older subject, CPD has recently become a strategic issue for businesses and gained meticulous consideration. However, there is no comprehensive review of CPD studies. This survey aims to fill this void by providing a review of key studies concerning CPD and its applications. The existing literature is analysed in three groups (CPD dynamics, partnership formation in CPD and CPD infrastructure) since CPD studies typically follow three characteristic paths. This study also aims to investigate the shortcomings of the existing literature and to provide future directions for research in the CPD domain. A conceptual framework derived from the literature review is presented, and it reveals the main issues on a strategic level to guide practitioners through their collaborative efforts.